A Theoretical Study of High Pressure Pool Boiling Heat Transfer on Engineered Surfaces - Dahariya, Smreeti; Betz, Amy R. (My University, 2017)
The performance of pool boiling is studied at high pressure on engineered surfaces. The studies were done for two different surfaces i.e., hydrophilic (CA < 90°) and hydrophobic (CA > 90°) surfaces. In addition, the bubble dynamics on a biphilic surface is also presented. Previous results are shown that the hydrophobic surfaces promote bubble nucleation at a lower super heat due to low surface energy is required. However, the effect of high pressure is sill need to be studied. The parametric studies were done for the size of active nucleation sites, departing bubbles and bubble release frequency under the influence of pressure. The current study will explain how the bubble dynamics affect the performance of boiling heat transfer.